2017
DOI: 10.1016/j.infbeh.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Differences in early cognitive and receptive-expressive neurodevelopment by ancestry and underlying pathways in Brazil and Argentina

Abstract: We examine disparities in early child cognitive and receptive-expressive skills by ethnic ancestry among infants aged 3 to 24 months from Brazil and Argentina. We employ unique data on the neurodevelopment of children who were seeking routine well-child care at a set of pediatric clinics in these countries. The sample included children who had normal birth outcomes and no major health complications, allowing us to focus on variation in neurodevelopment among children without major physical health limitations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Moreover, we estimated the difference in the risk of neurodevelopmental delay based on the geographical location of residence during the COVID-19 pandemic compared to before the pandemic. The geographical location of residence is an important indicator of children’s neurodevelopment, encompassing factors such as their behaviors, access to well-childcare centers, treatment of neurodevelopmental dysfunction, and the diagnosis of neurodevelopment [ 17 , 40 ]. Further, we found that the negative impacts on fine motor function, cognition, communication, social interaction, and self-care were more pronounced among urban children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we estimated the difference in the risk of neurodevelopmental delay based on the geographical location of residence during the COVID-19 pandemic compared to before the pandemic. The geographical location of residence is an important indicator of children’s neurodevelopment, encompassing factors such as their behaviors, access to well-childcare centers, treatment of neurodevelopmental dysfunction, and the diagnosis of neurodevelopment [ 17 , 40 ]. Further, we found that the negative impacts on fine motor function, cognition, communication, social interaction, and self-care were more pronounced among urban children.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that six studies included only children under two years of age [11][12][13][14][15][16] . For the most part, the target populations were children with normal development 11,12,15,[17][18][19][20][21][22][23][24][25][26][27][28] or children at-risk for delays 14,16,[29][30][31][32][33][34][35][36] . Two studies included children with confirmed disability diagnoses, such as cerebral palsy 37 and microcephaly 13 .…”
Section: What Do These Findings Mean?mentioning
confidence: 99%
“…A wide range of health professionals have administered this screening tool. Previously, several studies have used BINS for neurodevelopmental screening among preterm and young children [30][31][32][33]. In this regard, the subjects were Saudi infants with a corrected age of 21-24 months, who were born with a birth weight of 1000-1500 grams.…”
Section: Objectives and Outcomesmentioning
confidence: 99%